O desenvolvimento da equilibração majorante em crianças de educação infantil: um estudo de caso a partir do projeto Berçário de Hackers - Furini, Caroline da Silva (2017)
This paper manages several constituents processes of a great concept of Piaget‟s theory, the Equilibration Major, and how the activities that involves the Programming of Computers mayexpand the imbalance and posterior automatic or active regulations, providing the rebalancing to the cognitive system. The goal of investigation which gave it origin is identifying manifestations of Equilibration Major and processes that composes it, having by universe of research the Projeto Berçário de Hackers. A bibliographic study was performed, anchored to theoretical references that approach about the Equilibration Major and the Programming of Computers and in studies of Becker (2001), Bruner (2001), Montangero & Murice-Naville (1998), Papert (1994), Piaget (1975, 1976, 1978) and Veen & Vrakking (2009). Based on theoretical contribution elaborate, a seardh-action was developed in the Projeto Berçário de Hackers, happened at the Universidade de Passo Fundo, during 2016, of which they participated 19 children from 5 and 6 years, from Escola Municipal de Educação Infantil Cantinho Feliz. The data resulted from participant observations and transcriptions of video recordings and from the ScratchJr‟s software screen. For the exhibition, the actions were selected during the workshop of two students. It was observed that automatic and active regulations happened on both of students. The automatic regulations involved countless denials of the imbalances occasioned from the activities. From the moment that the denial happened and kept itself on stability to the moment of acceptance and option for change, we may realize that an important growth happened on the subjects. It is considered that may come the assistance from teachers and occur stimuli from materials, from software, and others, however, if the children do not act on pressure and get the learning of this entire route, the growing of this cognitive system does not find reception.